WRITING IN HISTORY: POTENTIAL OF THE INTERPERSONAL AND IDEATIONAL LINGUISTIC RESOURCES TO CONSTRUCT EVIDENCE - Oteíza, Teresa (Lenguas Modernas, 2018)
This article examines the process of incorporation of historical evidence in History majors’ written texts. This analysis is done from the complementary theoretical and methodological perspectives of systemic functional linguistics, in particular the APPRAISAL model and some ideational resources, in conjunction with the notions of ‘semantic density’ and ‘semantic gravity’ of the legitimation code theory. The analysis reveals that students construct a specialized language in the discipline that is sensitive to the primary and secondary bibliography consulted, as well as to the questions proposed by professors. In their historical explanations, students utilize language resources for building abstraction and generalization that tend to couple ideational and interpersonal meanings, generating an ‘axiological semantic density’. The resources for building ‘semantic density’ and ‘semantic gravity’ are combined in the discourse creating ‘semantic waves’ with a more monoglossic or heteroglossic orientation.